Événement technodiscursif et sociabilités numériques - Rejane Arce (Itinéraires)
We propose a reflection on the digital tools that give readers opportunities to share information, thus creating new spaces for discursivization. To illustrate our thinking, we chose multi-semiotic discursive materialities collected on the sites Le Nouvel Observateur, Radio France Internationale, Folha de São Paulo and Brasil de Fato. The goal is to establish a contrast between certain constituent aspects of textualities of the so-called traditional media and post-media, that is, the new contexts for profusion of discourses opened by digital social networks (DSN) focusing on the different ways to disseminate and participate in the making of a discursive event. Thus, we discuss the dimensions these digital sociabilities bring to the notion of event in a world where the linguistic form is associated with numerous untranslatable expressions by writing, which, however, contribute to the construction of sense of such writing.